2022
DOI: 10.1186/s12882-022-02901-9
|View full text |Cite
|
Sign up to set email alerts
|

Lambda light chain-induced monoclonal gammopathy of renal significance, manifesting with Fanconi Syndrome and osteomalacia

Abstract: Background Monoclonal gammopathy of renal significance (MGRS) encompasses a heterogeneous group of kidney diseases in which a monoclonal immunoglobulin secreted by a clone of B cells or plasma cells causes kidney damage without meeting the hematological criteria for malignancy. Among the various forms of involvement, MGRS can manifest as a proximal tubule disorder, such as Fanconi syndrome (FS), characterized by urinary loss of phosphate, glucose, amino acids, uric acid and bicarbonate. Few cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies have not supported the use of chemotherapy drugs, such as alkylating agents, because of their ineffectiveness in improving renal function and adverse effects, such as secondary malignancy. 5 However, as new drugs for multiple myeloma have become available, 11 case reports and 4 case series have shown the efficacy of chemotherapy, particularly bortezomib‐based regimens and ASCT to improve renal and tubular function 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 (summarized in Tables 2 and 3 ). Although these studies comprised a small case series and the definition of the renal outcome was variable, all reports showed that chemotherapy improved renal function or delayed the progression to end‐stage kidney disease, compared with that in the non‐chemotherapy group (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not supported the use of chemotherapy drugs, such as alkylating agents, because of their ineffectiveness in improving renal function and adverse effects, such as secondary malignancy. 5 However, as new drugs for multiple myeloma have become available, 11 case reports and 4 case series have shown the efficacy of chemotherapy, particularly bortezomib‐based regimens and ASCT to improve renal and tubular function 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 (summarized in Tables 2 and 3 ). Although these studies comprised a small case series and the definition of the renal outcome was variable, all reports showed that chemotherapy improved renal function or delayed the progression to end‐stage kidney disease, compared with that in the non‐chemotherapy group (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies did not support the use of chemotherapy such as alkylating agents because of its ineffectiveness in improving renal function and adverse effects such as secondary malignancy [5]. However, as new drugs for multiple myeloma have become available, 11 case reports and 4 case series have shown the efficacy of chemotherapy, particularly bortezomib-based regimens and ASCT to improve renal and tubular function [12][13][14][15][16][17][18][19][20][21][22] (summarized in Tables 2 and 3). Although these studies comprised a small case series, and the definition of the renal outcome was variable, all reports showed that chemotherapy improved renal function or delayed the progression to end-stage kidney disease, compared with that in the non-chemotherapy group (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical identification of LN can be challenging, being commonly discovered after careful examination of urine and renal function tests [1,3]. Monitoring the activity and/or control of LN is essential to prevent the progression of chronic kidney disease, which can have a negative impact on quality of life, functional dependence, comorbidities, and mortality risk [4][5][6].…”
Section: Introductionmentioning
confidence: 99%